APASL guidance on stopping nucleos(t)ide analogues in chronic hepatitis B patients - Kao, Jia-Horng; Jeng, Wen-Juei; Ning, Qin; Su, Tung-Hung; Tseng, Tai-Chung; Ueno, Yoshiyuki; Yuen, Man-Fung (Hepatology international, 2021)
Chronic hepatitis B virus (HBV) infection is currently incurable. Long-term treatment with potent and safe nucleos(t)ide analogs (NAs) can reduce hepatocellular carcinoma (HCC) and cirrhosis-related complications through profound viral suppression. However, indefinite therapy raises several crucial issues with pros and cons. Because seroclearance of hepatitis B surface (HBsAg) as functional cure is not easily achievable, a finite therapy including sequential 48-week pegylated interferon therapy may provide an opportunity to facilitate HBsAg seroclearance by the rejuvenation of exhausted immune cells. However, the cost of stopping NA is the high incidence of virological relapse and surge of alanine aminotransferase (ALT) levels, which may increase the risk of adverse outcomes (e.g., decompensation, fibrosis progression, HCC, or liver-related mortality). So far, the APASL criteria to stop NA treatment is undetectable HBV DNA levels with normalization of ALT; however, this criterion for cessation of treatment is associated with various incidence rates of virological/clinical relapse and more than 40% of NA-stoppers eventually receive retreatment. A very intensive follow-up strategy and identification of low-risk patients for virological/clinical relapse by different biomarkers are the keys to stop the NA treatment safely. Recent studies suggested that decreasing HBsAg level at the end-of-treatment to < 100–200 IU/mL seems to be a useful marker for deciding when to discontinue NAs therapy. In addition, several viral and host factors have been reviewed for their potential roles in predicting clinical relapse. Finally, the APASL guidance has proposed rules to stop NA and the subsequent follow-up strategy to achieve a better prognosis after stopping NA. In general, for both HBeAg-positive and HBeAg-negative patients who have stopped treatment, these measurements should be done every 1–3 months at the minimum until 12 months.